Modulatory Effects of Echinococcus multilocularis emu-let-7-5p on the Immunological Functions of RAW264.7 Macrophages - Jin, Xiaoliang; Li, Yating; Yang, Xing; Zheng, Yadong (Frontiers in Veterinary Science, 2021)
Echinococcus multilocularis is a zoonotic tapeworm with great medical significance. In E. multilocularis-infected mice, parasite-derived let-7-5p (emu-let-7-5p) is present in the sera, but its role remains unclear. Using qPCR, ELISA and flow cytometry, the immunomodulatory effects of emu-let-7-5p were in vitro investigated using RAW264.7 macrophages. Compared with the control, emu-let-7-5p significantly downregulated IL-1α (p < 0.05), but anti-inflammatory cytokine genes remained to be stably expressed in the treated macrophages. Moreover, significantly decreased expression of ripk1 and nf-kB, key components in the LPS/TLR4 signaling pathway, was also observed in the emu-let-7-5p-transfected cells (p < 0.05). Furthermore, CD40 was upregulated in these transfected cells (p < 0.05), while CD86, CD54 and CD80 remained unchanged compared that in the control. These results demonstrate a property of emu-let-7-5p in regulation of immune functions of macrophages, making it be possibly involved in the pathogen-host interplay during E. multilocularis infection.